1992
DOI: 10.3382/ps.0711145
|View full text |Cite
|
Sign up to set email alerts
|

Barley Inclusion and Avoparcin Supplementation in Broiler Diets.

Abstract: The clinical, pathological, and bacteriological findings of a mild form of necrotic enteritis (NE) in broiler chickens are presented. The term subclinical NE (SNE) is proposed for this condition. A diagnosis of SNE was based on the detection of macroscopically visible, focal necrotic lesions in the small intestinal mucosa. The ileal gut contents from SNE birds yielded increased numbers of Clostridium perfringens and reduced numbers of coliform bacteria. Reduced numbers of lactobacilli and streptococci were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
79
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(86 citation statements)
references
References 10 publications
7
79
0
Order By: Relevance
“…Two forms of NE (clinical and mild, i.e. sub-clinical) have been described and linked with lesions in the liver and cholangiohepatitis (Kaldhusdal & Hofshagen, 1992;Songer, 1996;Gholamiandehkordi et al, 2007;Olkowski et al, 2008). C. perfringens type A secretes different types of toxins such as alpha, beta 2, necrotic enteritis B-like toxin (NetB) and TpeL.…”
Section: Introductionmentioning
confidence: 99%
“…Two forms of NE (clinical and mild, i.e. sub-clinical) have been described and linked with lesions in the liver and cholangiohepatitis (Kaldhusdal & Hofshagen, 1992;Songer, 1996;Gholamiandehkordi et al, 2007;Olkowski et al, 2008). C. perfringens type A secretes different types of toxins such as alpha, beta 2, necrotic enteritis B-like toxin (NetB) and TpeL.…”
Section: Introductionmentioning
confidence: 99%
“…The proliferation of C. perfringens in the intestine and an increase in its toxin are considered the main cause of hemorrhagic necrosis of the intestinal mucosa (Dahiya et al 2006). A subclinical form has been associated with reduced feed conversion efficiency and retarded growth rate in birds (Kaldhusdal and Hofshagen 1992). This disease has been reported in most areas of the world where broilers are produced under intensive management conditions, and it has a significant economic impact on the poultry industry (van der Sluis 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The major factors for NE are the proliferation of the enteric bacterium Clostridium perfringens type A or C and production of exotoxins (Keyburn et al, 2008). However, many cofactors are usually required to promote overgrowth of C. perfringens in the intestinal tract and precipitate an outbreak of NE, including diet composition such as great amounts of wheat, barley, or rye (Kaldhusdal & Hofshagen, 1992;Riddell & Kong, 1992;Langhout, 1998). Numerous studies have shown that diets with high amounts of wheat and barley increase the intestinal content viscosity caused by water-soluble cell wall or non-starch polysaccharides, thereby resulting in a greater incidence of NE than corn-based diets (Kaldhusdal & Hofshagen, 1992;Kaldhusdal & Skjerve, 1996;Engberg et al, 2004;Jia et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, many cofactors are usually required to promote overgrowth of C. perfringens in the intestinal tract and precipitate an outbreak of NE, including diet composition such as great amounts of wheat, barley, or rye (Kaldhusdal & Hofshagen, 1992;Riddell & Kong, 1992;Langhout, 1998). Numerous studies have shown that diets with high amounts of wheat and barley increase the intestinal content viscosity caused by water-soluble cell wall or non-starch polysaccharides, thereby resulting in a greater incidence of NE than corn-based diets (Kaldhusdal & Hofshagen, 1992;Kaldhusdal & Skjerve, 1996;Engberg et al, 2004;Jia et al, 2009). The mechanism underlying this effect has been suggested to be that high intestinal viscosity reduces nutrient absorption by the host bird, decreases the rate of feed passage (Choct & Annison, 1992;Almirall & Esteve-Garcia, 1994), and may enhance mucus production (Langhout et al, 1999;Piel et al, 2005;Ito et al, 2009), which could lead to increased numbers of anaerobic bacteria in the intestine, particularly C. perfringens (Hü bener et al, 2002;Kocher, 2003;Engberg et al, 2004).…”
Section: Introductionmentioning
confidence: 99%